Răspuns :
Răspuns:
- a = 2
Explicație pas cu pas:
40 + 90 : [9 + 48 : (a + 6)] = 46
90 : [9 + 48 : (a + 6)] = 46 - 40
90 : [9 + 48 : (a + 6)] = 6
9 + 48 : (a + 6) = 90 : 6
9 + 48 : (a + 6) = 15
48 : (a + 6) = 15 - 9
48 : (a + 6) = 6
a + 6 = 48 : 6
a + 6 = 8
a = 8 - 6
a = 2
Răspuns:
a = 2
Explicație pas cu pas:
40 + 90 : [ 9 + 48 : ( a + 6 ) ]= 46
90 : [ 9 + 48 : ( a + 6 ) ] = 46 - 40
90 : [ 9 + 48 : ( a + 6 ) ] = 6
9 + 48 : ( a + 6 ) = 90 : 6
9 + 48 : ( a + 6 ) = 15
48 : ( a + 6 ) = 15 - 9
48 : ( a + 6 ) = 6
( a + 6 ) = 48 : 6
a + 6 = 8
a = 8 - 6
a = 2